2015
DOI: 10.1111/sms.12636
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of injuries in Brazilian elite handball players: A prospective cohort study

Abstract: The aim of this study was to investigate the incidence and risk factors for handball injuries in Brazilian elite handball players. Overall, 339 athletes from 21 handball teams who participated in the two main Brazilian championships were followed up during a season. In total, 312 injuries were reported by 201 athletes. The injury incidence rate during training was 3.7/1000 h, and during matches was 20.3/1000 matches. Ankle (19.4%, n = 46) and knee (13.5%, n = 32) were the body regions most affected by traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
101
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 26 publications
15
101
1
10
Order By: Relevance
“…Not all studies agree on susceptibility to injury by position, however, as in the present study wing players had the lowest injury rate (19.9 injuries per 1000 hours), while in another study18 wings had a higher injury incidence than goalkeepers and backs (93.0 to 53.9 and 88.0 injuries per 1000 hours, respectively) and Giroto et al 8 reported that male goalkeepers had a lower incidence of injuries compared with other playing positions.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Not all studies agree on susceptibility to injury by position, however, as in the present study wing players had the lowest injury rate (19.9 injuries per 1000 hours), while in another study18 wings had a higher injury incidence than goalkeepers and backs (93.0 to 53.9 and 88.0 injuries per 1000 hours, respectively) and Giroto et al 8 reported that male goalkeepers had a lower incidence of injuries compared with other playing positions.…”
Section: Discussioncontrasting
confidence: 53%
“…Studying risk factors of specific-sport injuries is necessary to provide a better understanding of the injury mechanism8 and therefore develop effective injury-prevention strategies 1. Despite some studies have identified that previous injury1 9 and lack of proprioception9 are risk factors for handball-related injuries, prospective studies aiming at investigating the risk factors of handball injuries are limited.…”
Section: Introductionmentioning
confidence: 99%
“…There was limited evidence for an increased risk of shoulder injuries in male high school and college lacrosse players compared with female players 40 42. There was limited evidence of no sex differences in shoulder injuries among elite handball players2 and college tennis players,48 and limited evidence of a decreased risk of shoulder injury among male college water polo players compared with female players 48…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there was limited evidence that female water polo players had a higher risk of shoulder injury than their male counterparts 48. There was also limited evidence of no sex differences in overuse injuries in handball 2. These findings on shoulder injuries in overhead sports, although varying between sports, are supported by several recent reviews that identified sex differences in the risk for concussions,69 groin injuries70 and ACL injuries 71…”
Section: Discussionmentioning
confidence: 98%
“…In fact, during two major Brazilian championships, out of a total of 339 athletes from 21 elite handball teams, 312 injuries were identified in 201 athletes, with ankle and knee being the most affected regions 4 . Considering the high rates of injuries in this sport, it is relevant to identify the variables that may predispose to the development of injuries in order to create prevention strategies in sports, such as muscular strength and postural balance.…”
Section: Introductionmentioning
confidence: 99%